Effect of Motorized Elephant-Assisted Therapy Program on Balance Control of Children with Autism Spectrum Disorder - Satiansukpong Nuntanee (2020)
© 2019 Satiansukpong Nuntanee and Sasat Daranee. Children with autism spectrum disorder (ASD) have poor balance, and this limitation has effects on their daily living activities. The purpose of this study was to create the motorized elephant-assisted therapy program (METP) and examine the effect of the METP on balance control improvement in individuals with ASD. Twenty participants, aged 8 to 19 years, were recruited from occupational therapy clinics around Chiang Mai city and were divided into 2 groups: control and experimental. Participants' balance control was tested by measuring their postural sways in a bipedal stance by using a Swaymeter under four conditions: "floor-eyes open," "floor-eyes closed," "foam-eyes open," and "foam-eyes closed." Pretests were administered one week before participation in the METP, and then, posttests were administered one week after completing the METP. Each participant took a 1.5-hour session of the METP, twice a week for a 4-week duration. In one session, 2 participants were assigned to work with two motorized elephants in 4 activities: washing the elephant, climbing up and down the elephant, riding the elephant, and playing a game while riding the elephant. Results showed that the pretest control and experimental groups were not significantly different in their balance control, but at posttest, the postural sway of the experimental group was significantly different from that of the control group in two conditions: floor-eyes open and floor-eyes closed. Their lesser anteroposterior range of postural sway showed that the experimental group gained balance control improvement. In conclusion, the finding of this study showed that the METP could be an alternative treatment method to facilitate better balance control in individuals with ASD.